2009
DOI: 10.1200/jco.2008.20.5096
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Aggressive End-of-Life Care for Taiwanese Cancer Decedents, 2001 to 2006

Abstract: Controlling for patient demographics and cormorbidity burden, EOL care in Taiwan was more aggressive for patients with cancer with highly malignant and extensive diseases, for patients with oncologists as primary care providers, or in hospitals with abundant health care resources. Health policies should aim to ensure that all patients receive treatments that best meet their individual needs and interests and that resources are devoted to care that produces the greatest health benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 39 publications
5
99
1
1
Order By: Relevance
“…A composite aggressive end-of-life care score has previously been reported, 10 with one point for each of the following 6 ASCO/NQF indicators in the last 30 days of life: two or more ER visits, two or more hospital admissions, more than 14 days of hospitalization, an ICU admission, death in a hospital, and use of chemotherapy. The total score ranged from 0 to 6, with a higher score indicating more aggressive care.…”
Section: Methodsmentioning
confidence: 99%
“…A composite aggressive end-of-life care score has previously been reported, 10 with one point for each of the following 6 ASCO/NQF indicators in the last 30 days of life: two or more ER visits, two or more hospital admissions, more than 14 days of hospitalization, an ICU admission, death in a hospital, and use of chemotherapy. The total score ranged from 0 to 6, with a higher score indicating more aggressive care.…”
Section: Methodsmentioning
confidence: 99%
“…A number of previous studies have identified variation in patients with cancers' ED attendance based on differing sociodemographic (predisposing) factors. [16][17][18] Our findings, however, suggest that rather than these factors per se influencing patients' ED use, it is the variation in symptom perception among these groups that ultimately determines the overall differences seen. This mechanism of action is further supported by previous studies that have identified variation in symptom perception by patient sociodemographics, including differences found across social class 33 and ethnicity.…”
Section: Discussionmentioning
confidence: 59%
“…[16][17][18] While these studies have identified a number of sociodemographic, environmental and clinical risk factors (eg, sex, age, ethnicity, socioeconomic status and type of cancer), evidence for why people with cancer decide to attend the ED is limited. 19 20 In order to address this issue and help guide development of future healthcare services, we conducted the following qualitative study.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…These indicators have been widely recognised and evaluated in several countries [5][6][7][8][9][10]. The most recent survey performed by Earle et al [6] involved 215,484 patients [65 years of age who died from cancer between 1991 and 2000 and who had been diagnosed while living in an area monitored by one of the Surveillance Epidemiology and End Results (SEER) registries.…”
Section: Therapeutic Aggressivenessmentioning
confidence: 99%